Leg extension power in heavyweight elite judo athletes - Sato, T.; Akimoto, H.; Takezawa, T.; Yokoyama, T.; Miyake, K.; Kawabata, K.; Kubota, H.; Masuchi, K.; Kasugai, A. (Research Journal of Budo, 2013)
This study compared the leg extension power of elite Japanese heavyweight male judoka with that of elite Japanese lightweight male judoka and clarified the exhibited characteristics.